MEDIASI KEPUASAN KERJA PADA PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Wirayuda, Sagap; Miranti, Miranti; Nurshandi, Muhamad; Damayanti, Irma (Desanta Publisher, 2025)
The purpose of this study is to analyze whether there is an influence of work discipline on employee performance, the influence of work discipline on work motivation, the influence of work motivation can affect employee performance. Is job satisfaction a mediating variable between work discipline, work motivation and employee performance. The research was conducted using the population and the sample in this study was 30 employees of PT Nikomas Gemilang Department of the Adidas Eva Pailon Section in Squad A. The sampling technique used in this study was saturated sampling or total non-random sampling. The entire population was sampled; The questionnaire uses the likert method 1-5. The data analysis technique in this study uses descriptive analysis and inferential analysis. For descriptive analysis, the author uses a computer-aided program with Smart PLS version 4. The results of the study showed that work discipline directly had a significant and positive effect on employee performance, work discipline had a significant and positive effect on work motivation, work motivation had a negative and insignificant effect on employee performance, and work discipline had a negative and significant effect on employee performance mediation. Indirectly, job satisfaction mediation does not mediate the relationship between motivation variables and employee performance variables.